Taste Profiling Of Centella Asiatica By A Taste Sensor. - Shafiqul Islam, A.K.M.; Ismail, Zhari; Ahmad, Mohd Noor; Othman, Prof.Madya Abdul Rahman; Dharmaraj, Saravanan; Shakaff, A.Y. (2003)
A taste sensor was used for organoleptic profiling and quality evaluation of Centella asiatica extracts and isolates on the basis of basic tastes i.e., sweett sour, bitter, salty and umami.